Penormaan Pengawasan Izin Lingkungan dalam Pencegahan Pencemaran dan Kerusakan Lingkungan Hidup dalam Eksploitasi Sumber Daya Alam - Listiyani, Nurul; Akbar Hayat, Muzahid; Mandala, Subianta (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2018)
In environmental protection and management, the main effort is to prevent pollution and damage on environment instead of repressing the damages occurred. Permit is one of preventive measures and becomes a principle in Administrative Law. Permits can be seen as governmentâ€™s tool as judicial preventive and used as an administrative instrument to control people's behavior. Environmental permit can be seen as preventive measure, because it always related to orders and obligations that must be obeyed by the holder. On the other hand, environmental permit also function as repressive instrument to counter environmental problems due to human activities, including mining. The normâ€™s obscurity on the supervision of environmental permits in in Law No. 32 Year 2009 on Environmental Protection and Management (hereafter will refer as UUPPLH) is an indicator for the lack of the objective results.Based on type, this researchÂ focuses the study on the Environmental permit as an absolute requirement. Normatively, the principle of environmental permit as stipulated in Environmental Law regulates that every business and/or activity which required an Environmental Impact Analysis document or UKL-UPL should also hold an environmental permit. The purpose of Environmental permits is to maintain the preservation of environmental functions while also prevent and counter environmental pollution and damage due to human activities. Based on this construction, permits plays a very important role in environmental activity. Exploitation of natural resources has a significant impact on the environment, thus based on Article 22 paragraph (1) of Environmental Law these activities requires an Environment Impact Analysis. Important impacts as detailed in Article 22 paragraph (2) at empirical level still occurs so the goal of preventing pollution and damage as the objective of environmental permits still has not been achieved.